A viscoelastic-viscoplastic constitutive model for glassy polymers informed by molecular dynamics simulations. (September 2021) - Zhao, Wuyang; Ries, Maximilian; Steinmann, Paul; Pfaller, Sebastian
Highlights: A novel VE-VP constitutive model for glassy polymers is calibrated by MD simulations. Different contributions to inelasticity in polymers are isolated in MD simulations. An interpretation of the physics behind the constitutive model is provided. The constitutive model is appropriate for the FE parts of MD-FE coupling simulations. Abstract: This contribution presents a phenomenological viscoelastic-viscoplastic constitutive model informed by coarse-grained (CG) molecular dynamics (MD) simulations of pure glassy polystyrene (PS). In contrast to experiments, where viscoplasticity is caused by various effects simultaneously, these effects can be decomposed in MD simulations by adjusting the MD system. In the MD simulations considered here, neither bond breakage nor cross-links are introduced; instead, we focus on the intermolecular interaction of polymer chains. We employ a thermo-dynamically consistent generalized Maxwell framework parallelly comprising an elastic, a viscoelastic, and several elasto-viscoplastic modules with different yield stress to capture the viscoelastic and the viscoplastic mechanical behavior simultaneously. The yield stresses decrease with the maximum deformation the MD system has experienced. The constitutive model presented here is based on 10 material parameters, which can be identified by a few data sets and fits well the CG MD simulations of PS under uniaxial and biaxial deformation with time-proportional and cyclic loading conditions in a wide range of strain rates (0.1%/ns–20%/ns).